Pemanfaatan Model LandGem Untuk Potensi Gas Metana di TPAS Sekoto Menjadi Sumber Energi - Sekar Nur Habibah Mahiroh; R Mohammad Alghaf Dienullah; Abdillah Akmal Karami; Sekarsari Wibowo (Jurnal Serambi Engineering, 2025)
Landfills generate methane gas (CH₄) as a result of the anaerobic decomposition of organic waste. This gas has the potential to serve as a renewable energy source if managed properly. This study aims to analyze the methane gas emission potential from the Sekoto landfill using the Landfill Gas Emission Model (LandGEM) and convert it into electricity and LPG. Annual waste generation data from 2021 to 2026 was used as input for the LandGEM model to estimate methane gas emissions. The modeling results indicate that peak methane production will occur in 2027, with a total of 4,247,951 m³/year. The potential electrical energy generated from this methane gas reaches 349,421,156.64 kWh per year, equivalent to 39,888.26 MWh. Additionally, the potential conversion of methane gas to LPG is estimated at 1,954,057.46 kg of LPG per year or approximately 5,353 kg per day. Utilizing methane from the Sekoto landfill as an alternative energy source not only contributes to renewable energy supply but also reduces greenhouse gas emissions that impact global warming. With a more efficient gas harvesting system and adequate processing infrastructure, methane gas can be converted into a more beneficial energy source for the community. This study confirms that optimizing landfill gas management can enhance energy sustainability while mitigating the environmental impact caused by methane emissions.